The Epontic Algal Community of the Ice Edge Zone and Its Significance to the Davis Strait Ecosystem - Booth, J.A. (ARCTIC, 1984)
The ice algae community in the dynamic outer edge zone of the Davis Strait pack ice was investigated in April-May 1978. Surveys of the epontic community were made using a remote camera system, a fibrescope, an ice corer, and in situ C14 incubation chambers. The undersurfaces of the floes were generally flat, containing slight undulations and small depressions of up to 10 cm. In the bottom few centimetres a transition was noted from hard ice to more fragile, but still firm, crystalline ice. Epontic flora was highly patchy and almost entirely restricted to the bottom few centimetres of the floes. Average concentrations in the bottom 6 cm of ice was 10.24 mg chl a/cu m. The pack ice bloom occurred in April and May with a peak occurring in May. The maximum primary production rates of 2.4 mg C/sq m/d occurred at a light intensity of 1.8 mu epsilon/sq m/s. Photosynthesis appeared to be inhibited at light levels above 20 mu epsilon/sq m/s. The dominant genera of the epontic flora were Navicula, Nitzschia, and Pleurosigma; species composition of the epontic algal community differed significantly from that of the plankton. Two other ice algae communities were noted; a "sandwich" community in the middle of an ice floe, dominated by Asteromphalus hookeri and Thalassiosira gravida; and a floe surface community which was on one occasion observed being seeded from the plankton. The total contribution of the epontic algae to the primary production of the Davis Strait was estimated to be approximately 7x10**7g C/y, or less than 1% that of the phytoplankton. The contribution may still be important, however, as it precedes the phytoplankton bloom and is the only algal concentration under heavy pack ice.Key words: Davis Strait, pack ice, epontic, primary production, ice algae Mots clés: détroit de Davis, banquise, production primaire, algue glaciale